Meningkatkan Aktivitas dan Hasil Belajar Siswa Melalui Penerapan Model Pembelajaran Jigsaw Dalam Mata Pelajaran IPS di Kelas VI SD Negeri Siem - Desy Ramazani; M. Husin; Sulaiman Sulaiaman (Universitas Syiah Kuala, 2023)
The objective of this research is to enhance student engagement and evaluate academic achievement by implementing the Jigsaw learning approach in the context of social studies for sixth-grade students at SD Negeri Siem. The present study employs the Classroom Action Research methodology to investigate the effectiveness of the Jigsaw learning model. The investigation was conducted during the first semester of the academic year 2022/2023, comprising three distinct phases. The research comprised a sample of 29 female and 19 male sixth-grade students from SD Negeri Siem. Two common techniques for gathering data are testing and observation. The observation sheets and test questions serve as instruments for collecting data. The employed methodology for data analysis involves the utilization of descriptive qualitative analysis. The study's findings indicate a rise in social studies educational engagement and achievements among sixth-grade students at SD Negeri Siem. During Cycle I, the teacher's activity received a score of 72.5, while the student activity received an average score of 51.9 with satisfactory criteria. The average grade for student learning outcomes was 59.1. During Cycle II, the teacher demonstrated an activity score of 85, while the students exhibited an average activity score of 67, meeting the good criteria. As a result, the average grade for student learning outcomes was 77.5. During the third cycle, the teacher's activity was rated at 92.5, while the student activity received an average score of 75.8, which was deemed to be of high quality. As a result, the average class score for student learning outcomes was 84.1.